Poly(eriochrome black T) modified electrode for electrosensing of methdilazine. (December 2020) - Shetti, Nagaraj P.; Ilager, Davalasab; Malode, Shweta J.; Monga, Divya; Basu, Soumen; Reddy, Kakarla Raghava
Abstract: The current research work is based on the development of an electrode modified by using an indicator, poly(eriochrome black T) (poly-EBT) for the determination of methdilazine hydrochloride (MDH). Excellent electrocatalytic, semiconducting properties of poly-EBT influences the enhanced peak current of MDH. Different voltammetric techniques like cyclic, square wave voltammetry were employed. The association happens among metallochromic indicators, poly-EBT, and positively charged MDH at the surface of the working electrode. The characterization of poly-EBT modified CPE was studied with the help of atomic force microscopy technique (AFM). The concentration of MDH was determined using poly-EBT modified electrode in the wide concentration range 1.0 × 10 −7  M to 0.5 × 10 −4  M with LOD value of 2.57 × 10 −8  M. Poly-EBT modified electrode showed enhanced the sensitivity and selectivity for the determination of MDH in human urine samples and pharmaceutical dosage forms. Graphical abstract: Image 1